The Effect of Ethnoscience Based Contextual Learning Toward Students’ Learning Activity (Journal of Primary Education, 2019)
The 21st century of learning refers to the development of students’ activeness. One of the effort to improve is the students activeness accompanied with contextual learning based ethnoscience that affect the activity of students’ learning. The purpose of this study was to determine the effect of the implementation of contextual learning based etnosains on the students' learning activity. The location of the study was SDN Kauman and SD N 5 Mulyoharjo, Jepara. The type of the study was a mixed method, with embedded experimental models design. The total sample in this study were 61 students. The data were done by using test method, observations, questionnaires, and documentation. The result of this study is the profile of the contextual learning on the activeness of students. There is a significant effect of contextual learning based ethnoscience on the students' learning activeness. The students' learning activeness is categorized as high category with the percentage of 91.09% for SD N Kauman and 89% for SD N 5 Mulyoharjo. The conclusion of this study is that the contextual learning based ethnoscience has significant effect on the students' learning activeness.